IDENTIFIKASI PERILAKU DAN KARAKTERISTIK PESERTA DIDIK DI SD NEGERI 4 SUKASARI KOTA TANGERANG - Ina Magdalena; Nabela Kanti Utami; Rahma Mutiara (CV. ADIBA ASIHA AMIRA, 2023)
Identifying the initial behavior and characteristics of students is a process that teachers must go through in designing their lessons. There are two approaches to choose from. First, students adjust to the subject matter. Second, on the other hand, the subject matter is adapted to students. Each student and class group has different characters and abilities, so that the same treatment of all students and class groups will actually result in a less than optimal learning process. Therefore one of the important stages in the learning planning process is to analyze student character. Where the characteristics of students at the elementary school level are different from those at the secondary school level. Their way of thinking, perceptions and ways of dealing with problems are very different.